النظـــــام الهيكلــــــي لسلطـــــة الوطنية المستقلــــة للانتخــــابـــات - دراسة مقارنة بين القانون الجزائري والقانون التونسي- - كمرشو, الهاشمي (unuversity of eloued- جامعة الوادي, 2022)
ملخص: أنشئت السلطة الوطنية المستقلة للانتخابات بالجزائر بموجب المادة 200 من الدستور الجزائري والقانون العضوي رقم 21-01 المتعلق بنظام الانتخابات ، حيث تشرف على تنظيم العملية الانتخابية من خلال تحديد أصحاب الحق في الاقتراح و استقبال ملفات الترشح و إعلان النتائج بكل حياد وشفافية. و يقوم تنظيمها الهيكلي على جهاز تداولي ممثل في مجلس السلطة عدده عشرون عضو يعينهم رئيس الجمهورية بما فيهم الرئيس و لها امتدادات على مستوى الولايات و البلديات والمثليات الدبلوماسية والقنصلية بالخارج. أما في تونس فتشرف الهيئة الوطنية العليا للانتخابات على العملية الانتخابية التي أنشئت بموجب الفصل 126 من الدستور التونسي و قرار الهيئة العليا المستقلة للانتخابات عدد 12 لسنة 2014 المؤرخ في 16 جويلية 2014،حيث يتكون مجلسها الوطني من 09 أعضاء مستقلين ومحايدين من ذوي الكفاءة و النزاهة لمدة ستة سنوات يجدد ثلث أعضائها كل سنتين يتم تعيينهم من قبل البرلمان وينتخبون من بينهم رئيس، ولهم امتدادات جهوية على مستوى الولايات وامتدادات فرعية وقنصلية بالخارج. Abstract: The Independent National Authority for Elections was established in Algeria under Article 200 of the Algerian Constitution and Organic Law No. 21-01 related to the electoral system. It supervises the organization of the electoral process by identifying the holders of the right to propose, receive candidacy files, and announce the results with impartiality and transparency. Its structural organization is based on a deliberative body represented in the Council of the Authority, numbering twenty members, appointed by the President of the Republic, including the President, and it has extensions at the level of states, municipalities, and diplomatic and consular lesbians abroad. In Tunisia, the Supreme National Elections Authority supervises the electoral process, which was established under Article 126 of the Tunisian Constitution and the decision of the Independent High Authority for Elections No. 2014-12 dated July 16, 2014. Its National Council consists of 09 independent and impartial members of competence and integrity for a term of six. Years One-third of its members are renewed every two years. They are appointed by Parliament and elect from among them a president. They have regional extensions at the state level, as well as subsidiary and consular extensions abroad.
مقال
Keywords: السلطة الوطنية ؛ الهيئة العليا ؛ الانتخابات؛الجزائر؛ تونس; national authority; High Authority ; elections; Algeria; Tunisia